Spatial Regulation of Acceptor Units in Olefin‐Linked COFs toward Highly Efficient Photocatalytic H2 Evolution - Zhao, Zhengfeng; Chen, Xuepeng; Li, BaoYing; Zhao, Shu; Niu, Liwei; Zhang, Zhenjie; Chen, Yao (Advanced science, 2022)
Covalent organic frameworks (COFs)‐based photocatalysts have received growing attention for photocatalytic hydrogen (H2) production. One of the big challenges in the field is to find ways to promote energy/electron transfer and exciton dissociation. Addressing this challenge, herein, a series of olefin‐linked 2D COFs is fabricated with high crystallinity, porosity, and robustness using a melt polymerization method without adding volatile organic solvents. It is found that regulation of the spatial distances between the acceptor units (triazine and 2, 2'‐bipyridine) of COFs to match the charge carrier diffusion length can dramatically promote the exciton dissociation, hence leading to outstanding photocatalytic H2 evolution performance. The COF with the appropriate acceptor distance achieves exceptional photocatalytic H2 evolution with an apparent quantum yield of 56.2% at 475 nm, the second highest value among all COF photocatalysts and 70 times higher than the well‐studied polymer carbon nitride. Various experimental and computation studies are then conducted to in‐depth unveil the mechanism behind the enhanced performance. This study will provide important guidance for the design of highly efficient organic semiconductor photocatalysts. The spatial regulation of acceptor units in olefin‐linked COFs to match the charge carrier diffusion length can dramatically promote the exciton dissociation, hence leading to outstanding photocatalytic H2 evolution performance. This study endows COFs with great potential to serve as excellent platforms for solar energy conversion to H2 with an apparent quantum yield of 56.2% at 475 nm.